2019
DOI: 10.1038/s41598-019-38526-6
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the NHEJ pathway by DNA-PKcs inhibitor NU7026 prevents degradation of HBV cccDNA cleaved by CRISPR/Cas9

Abstract: Chronic hepatitis B is a severe liver disease caused by hepatitis B virus (HBV) infection. Covalently closed circular DNA (cccDNA), a super-spiralized, double-stranded form of the HBV genome, is the major determinant of viral persistence. CRISPR/Cas9 nucleases have been recently shown to introduce double-stranded DNA breaks into HBV cccDNA. The inflicted damage results predominantly in erroneous repair of cccDNA by non-homologous end-joining (NHEJ). NHEJ has been suggested to enhance anti-HBV activity of CRISP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 68 publications
3
31
0
Order By: Relevance
“…Additional experiments are needed to rule out whether cellular effects such as cell division, migration, or differentiation are affected in long term tissue renewal. The homeostatic effects of PARylation may be overshadowed by the dominant suppression of alternative enjoining through the core DNA repair signaling pathways (i.e., nonhomologous end joining and homologous recombination) [55][56][57]. Nonetheless, the finding that Smed-PARP-3 is a regulator of regeneration is consistent with our previous work, where we found its expression sharply activated within the first three hours post-injury [20] and recent findings by the Aboobaker group [22].…”
Section: Discussionsupporting
confidence: 91%
“…Additional experiments are needed to rule out whether cellular effects such as cell division, migration, or differentiation are affected in long term tissue renewal. The homeostatic effects of PARylation may be overshadowed by the dominant suppression of alternative enjoining through the core DNA repair signaling pathways (i.e., nonhomologous end joining and homologous recombination) [55][56][57]. Nonetheless, the finding that Smed-PARP-3 is a regulator of regeneration is consistent with our previous work, where we found its expression sharply activated within the first three hours post-injury [20] and recent findings by the Aboobaker group [22].…”
Section: Discussionsupporting
confidence: 91%
“…HBV-DNA can be integrated into host genomic DNA and cause insertion mutations or other genomic instabilities [38,39]. Studies have shown that DNA double strand breaks (DSBs) induced by DNA damage are potential targets for HBV-DNA integration [40][41][42]. The body repairs DSBs through two major repair pathways: homologous recombination (HR) and non-homologous end-joining (NHEJ) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, HBV cccDNA is an optimal target for nuclease gene editing, due to its episomal minichromosome configuration and sequence stability. More specifically, the efficacy of CRISPR/Cas9 for cleavage and inactivation of the cccDNA, as well as inhibition of hepatocarcinogenesis, has been reported [ 34 , 35 ].…”
Section: Direct Acting Antiviralsmentioning
confidence: 99%